Vacuum high-temperature refining of carbon materials using NaCl vapors as a transport and reaction medium - Kravtsov, Ya.V.; Gurin, I.V.; Bukolov, A.N.; Gribanov, Yu.A.; Kolosenko, V.V. (Вопросы атомной науки и техники, 2020)
One of the main requirements to carbon materials is their purity. The authors have proposed and experimentally tested a new method for vacuum-thermal refining of carbon materials using NaCl vapor as an activator. It is experimentally confirmed that this method allows increasing the refining process efficiency and decreasing the energy consumption. The proposed method can be an alternative to modern methods of chlorine- and fluorine thermal refining that permits to exclude the use of hazardous reagents.